Fructanogenic traits in halotolerant Bacillus licheniformis OK12 and their predicted functional significance - TOKSOY ÖNER, EBRU (WILEY, 2021)
Aims Isolating a novel bacterial source of fructan from a saltern and analysis of its genome to better understand the possible roles of fructans in hypersaline environments. Methods and Results Bacteria were isolated from crude salt samples originating from camalti Saltern in Western Turkey and screened for fructanogenic traits in high-salt and sucrose-rich selective medium. Exopolysaccharide accumulated in the presence of sucrose by isolate OK12 was purified and chemically characterized via HPLC, FT-IR and NMR, which revealed that it was a levan-type fructan (beta-2,6 linked homopolymer of fructose). The isolate was taxonomically classified as Bacillus licheniformis OK12 through 16S rRNA gene and whole-genome sequencing methods. Strain OK12 harbours one levansucrase and two different levanase genes, which altogether were predicted to significantly contribute to intracellular glucose and fructose pools. The isolate could withstand 15% NaCl, and thus classified as a halotolerant. Conclusions Fructanogenic traits in halotolerant B. licheniformis OK12 are significant due to predicted influx of glucose and fructose as a result of levan biosynthesis and levan hydrolysis, respectively. Significance and Impact of the Study Fructans from the residents of hypersaline habitats are underexplored compounds and are expected to demonstrate physicochemical properties different from their non-halophilic counterparts. Revealing fructanogenic traits in the genome of a halotolerant bacterium brings up a new perspective in physiological roles of fructans.
Keywords: fructan; halotolerant; hypersaline; levan; polysaccharide; whole‐ genome analysis